A sustainable campus between theory and practice Qassim University campus - a case study - Sherif El Sayed (Journal of Architecture, Art & Humanistic Science, 2022)
A sustainable building is that building in which there are many applications and practices that take into account environmental considerations in all or some stages of construction, starting from design, then implementation, to operation and maintenance, in addition to achieving energy efficiency, resource and water use, As well as the quality of the internal life of the building, and the impact of all this on the surrounding environment. Likewise, the university campus, whose sustainability is achieved by applying best practices inside and outside it as well, began with the design of the university's buildings, including various environmental elements, through joint work and coordination between the various colleges of the university, and the effective organization between the administrative and executive departments to achieve this, and ended with the effective participation of the university in its various departments With the local community, and the world as well.Therefore, a sustainable campus must have many applications for reducing internal global warming rates, saving energy, rationalizing water consumption, fuel, costs, and other applications that over time will improve the public health of users, and this will in turn be reflected in the quality of the process. Educational and other activities related to this, in addition to the positive effects that this will have in the future on the performance and behavior of students, and all workers on campus.By reviewing previous studies, it was found that there are three main axes that a sustainable university must apply and develop continuously, these axes include both the administrative axis of the university, the axis of sustainable participation of the university internally or externally, in addition to the environmental axis related to the study of architectural applications implemented inside the campus. Therefore, the main objective of this research is to study the three axes of educational sustainability, discuss all the points related to them within the university campus, and present what has been achieved in one of the Saudi universities (Qassim University - Al-Mulida headquarters) for examination, verification, and comparison in order to know the strengths Weakness, and then access to the best corrective practices that must be taken for better performance and efficiency. And coming up at the end of the research with a set of findings and recommendations that must be followed to improve the environmental performance of the university to become a more positive and environmentally friendly campus in the near future.